A collagen-based bi-layered composite dressing for accelerated wound healing. Issue 1 (February 2022) - Sun, Leilei; Li, Laihao; Wang, Yueqi; Li, Mingbo; Xu, Shumin; Zhang, Chengpeng
Abstract: Aim of the study: The aim of the study was to fabricate collagen-based composite dressings, evaluate the efficiency for wound healing and reveal the mechanism of promoting wound healing. Materials and methods: An innovative bi-layered composite wound dressing was developed using two marine biomacromolecules (collagen and chitosan). Full-thickness skin defect model was performed to evaluate the wound healing activity in vivo . The levels of inflammatory cytokines including tumor necrosis factor alpha (TNF-α), interleukin (IL-1, IL-6, IL-8) and growth factors like transforming growth factor beta (TGF-β), vascular epidermal growth factor (VEGF) and basic fibroblast growth factor (bFGF) were quantified by ELISA assays. The total amount of collagen was quantified by hydroxyproline content. The proliferation and viability of fibroblast cells cultured on collagen sponges were determined by CCK-8 assay. Results: The results of wound closure and histopathological analysis indicated that non-crosslinked collagen-based bi-layered composite dressing stimulated wound healing, accelerated re-epithelialization and accomplished wound healing within a time span of 28 days. The results of levels of inflammatory cytokines and growth factors showed that collagen-based composite dressings could reduce the inflammatory response and upregulate growth factors levels to accelerate the wound healing. The results of hydroxyproline content and CCK-8 assay indicated that collagen-based composite dressings could also promote collagen synthesis and fibroblasts viability and proliferation. Conclusion: The non-crosslinked collagen-based bi-layered composite dressing could be applied for an efficient and ideal wound dressing. Therefore, the findings provided the essential theoretical basis for the potential of collagen-based composite dressing applied in wound healing fields. Graphical abstract: Image 1 Highlights: Non-crosslinked collagen dressing healed faster than that cross-linked by EDC/NHS. Dressings regulated inflammatory cytokines to reduce inflammatory response. Collagen dressings upregulated growth factors levels to accelerate wound healing. Collagen dressings facilitated collagen synthesis during wound healing. Collagen dressings promoted fibroblasts viability and proliferation.